"Shame on you!" : competing narratives of the nation in the Laoxikai Incident and the Tianjin anti-French campaign, 1916-1917 - Chen, Songchuan. (2013)
This article examines the anti-French campaign triggered by the Laoxikai incident — a dispute in 1916‐17 over lands bordering the French concession in Tianjin. The incident was a focal point for competing narratives of the nation, each drawing on traditions and inspirations that implied divergent futures for China. Constitutional monarchism, true monarchism, republicanism, and Christianity all played into the power struggles of the 1910s. This article also addresses the role of violent coercion in the incident, in which nationalism began to legitimate “punishment” of Chinese who continued working with the French. The nationalists felt shame on behalf of their nation, and through public humiliation they forced Chinese who appeared indifferent to the nation to share in the national shame. This development accelerated a trend of nationalistic violence and the discourse of “national humiliation”.